The Influence of the RME Learning Model on Mathematical Problem Solving and Communication Skills in Mathematics Learning in Students of SMP 1 Bangkinang City (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to examine the effect of implementing the Realistic Mathematics Education (RME) learning model on students’ mathematical problem-solving skills and mathematical communication abilities at SMP Negeri 1 Bangkinang Kota. The study emphasizes how context-based learning grounded in real-life situations can enhance students’ conceptual understanding, higher-order thinking skills, and their ability to communicate mathematical ideas systematically and effectively. Research Method: This study employed a quasi-experimental design using a Pretest–Posttest Control Group Design. The research sample consisted of 40 eighth-grade students of SMP Negeri 1 Bangkinang Kota, divided into two groups: an experimental group (20 students) taught using the RME model and a control group (20 students) taught using conventional mathematics instruction. Data were collected through a mathematical problem-solving test and a rubric-based assessment of mathematical communication skills. Data analysis was conducted using descriptive statistics and inferential statistics, specifically an independent samples t-test, after fulfilling the assumptions of normality and homogeneity. Research Findings: The results indicate a significant difference between the experimental and control groups in terms of mathematical problem-solving skills and mathematical communication abilities. The posttest scores of students in the experimental group were significantly higher than those of the control group. These findings demonstrate that the implementation of the RME model is effective in improving students’ mathematical problem-solving and communication skills. Novelty: This study clarifies the novelty of RME by explaining the classroom mechanism that integrates contextual problem exploration, group discussion, and student presentations. Through these processes, students simultaneously develop mathematical communication and problem-solving skills within collaborative and reflective learning activities.